Credit controls as an escape from the trilemma. The Bretton Woods experience†. (21st February 2018) - Monnet, Eric
Abstract: The Mundell "trilemma" is widely used to discuss capital controls and monetary policy autonomy under Bretton Woods. Without denying its usefulness, this paper highlights two facts at odds with assumptions underlying the "trilemma" argument. First, conflicts between internal and external objectives were uncommon. Second, the use of quantitative credit controls allowed central banks to disconnect their interest rate from their monetary policy stance. This was considered by contemporaries as a way to escape international constraints. Capital controls were imposed to complement credit controls. Interest-rate spreads were neither a good measure of capital controls nor of central bank autonomy.